Ginseng supplementation and vascular function: a systematic review and meta-analysis of clinical trials - Ayda Esmaeili; Naser Khalili; Nastaran Najafi; Fatemeh Hajizadeh-Sharafabad (BMC Complementary Medicine and Therapies)
Abstract Background Ginseng is a source of pharmacologically active compounds with cardioprotective properties. The aim of the current systematic review and meta-analysis was to investigate the effect of ginseng on vascular function. Methods Electronic databases, including PubMed, ISI Web of Science, Scopus, and Google Scholar were searched using relevant keywords from inception until February 2025. The eligibility criteria for a full-text review of papers consisted of clinical trials involving subjects aged ≥ 15 years who consumed ginseng and evaluated at least one of the cardiac function markers: flow-mediated dilation (FMD), pulse wave velocity (PWV), augmentation index (AIx), and circulating biomarkers of vascular function. Results From a total of 328 initial search records, 13 randomized controlled trials were included in the study. Pooled analysis showed a significant increase in FMD level (effect size: 5, SMD: 0.571%, 95% CI: 0.198, 0.943, P = 0.003), and endothelium-derived nitric oxide levels (effect size: 4, SMD: 0.30, 95% CI: 0.01, 0.59, P = 0.045) as well as a significant decrease in PWV (effect size: 7, SMD: ‒0.29 cm/s, 95% CI: ‒0.51, ‒0.06, P = 0.014). No significant effect was observed in AIx (effect size: 9, SMD: ‒0.53%, 95% CI: ‒1.08, 0.03, P = 0.063) following ginseng intake. Conclusions The overall results revealed beneficial effects of ginseng on endothelial function and arterial stiffness, as measured by PWV, while it did not change AIx. Further studies are recommended to investigate the effects of ginseng on vascular function.